Identifying people at higher risk of melanoma across the U.K.: a primary-care-based electronic survey - Usher-Smith, Juliet A.; Kassianos, Angelos P.; Emery, Jon David; Abel, Gary; Teoh, Z.; Hall, Susan; Neal, Richard; Murchie, Peter; Walter, Fiona (My University, 2017)
Background: Melanoma incidence is rising rapidly worldwide among white populations. Defining higher-risk populations using risk prediction models may help targeted screening and early detection approaches. Objectives: To assess the feasibility of identifying people at higher risk of melanoma using the Williams self-assessed clinical risk estimation model in U.K. primary care. Methods: We recruited participants from the waiting rooms of 22 general practices covering a total population of > 240 000 in three U.K. regions: Eastern England, North East Scotland and North Wales. Participants completed an electronic questionnaire using tablet computers. The main outcome was the mean melanoma risk score using the Williams melanoma risk model.
Keywords: Melanoma; Williams self-assessed clinical risk estimation model